Cloud and Aerosol Distributions From SAGE III/ISS Observations. Issue 23 (9th December 2021) - Schoeberl, Mark; Jensen, Eric; Wang, Tao; Taha, Ghassan; Ueyama, Rei; Wang, Yi; DeLand, Matthew; Dessler, Andrew
Abstract: We describe our Solar Aerosol and Gas Experiment (SAGE) III/ISS cloud detection algorithm and observations. We identify three types of clouds: visible cirrus (extinction coefficient > 3 x 10 −2 km −1 ), subvisible cirrus (extinction coefficient between 3 x 10 −2 km −1 and 10 −3 km −1 ), and very low extinction cloud‐aerosol mixtures (extinction coefficient between 10 −3 km −1 and 10 −4 km −1 ). Visible cirrus cannot be quantitatively measured by SAGE because of its high extinction, but we infer the presence of cirrus through the termination of the SAGE vertical scan. We then assume that cirrus layers extend 0.5 km below the scan termination height. SAGE cirrus cloud fraction estimated in this way is in qualitative agreement with Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) measurements. Analyzing 2018–2020 SAGE III/ISS data, we find that visible cirrus and subvisible cirrus have nearly equal abundance in the tropical upper troposphere and the average cloud fraction is about 25%. At 16 km, the highest concentration of visible cirrus and subvisible cirrus is over the Tropical West Pacific, central Africa, and central South America during boreal winter. Latitudinal gaps in zonal mean cloud fraction are aligned with descending branch of the residual mean circulation. Using tropopause relative coordinates, we show that maximum cloud‐top heights are consistently restricted to a narrow region near the tropopause. The aerosol extinction fields also show the latitudinal gaps coincident with the descending residual circulation. We identify four anomalous aerosol extinction periods that can be tentatively assigned to significant volcanic or fire events. Plain Language Summary: The SAGE III/ISS instrument records the attenuation of sunlight as the sun sets or rises across the atmospheric limb. We can use this attenuation to gain information on upper tropospheric and lower stratospheric clouds and aerosols. We find that the upper tropical troposphere has nearly an equal abundance of visible and subvisible cirrus. These clouds are forming where the tropical convection occurs and where the atmosphere is upwelling due to radiative heating. We also find that the there is a decrease in cloud distributions on the flanks of the tropics associated with downwelling circulation. Aerosol concentration shows the same decrease. We also show that aerosols have a higher concentration where volcanoes and fires have injected material into the stratosphere. Key Points: Solar Aerosol and Gas Experiment III/ISS can detect subvisible cirrus and infer the presence of visible cirrus Subvisible and visible cirrus are concentrated in the tropical upper troposphere The descending residual circulation that flanks the tropics produces reduced cloud and aerosol concentrations